An appraisal of emerging second line therapies for metastatic colorectal cancer. (1st February 2021) - Smolenschi, Cristina; Perret, Audrey; Dall'Armellina, François; Boige, Valerie; Malka, David; Hollebecque, Antoine; Ducreux, Michel
ABSTRACT: Introduction: Despite a significant improvement in overall survival over the last 15 years, colorectal cancer remains a major public health problem worldwide. Much effort has been made to develop an optimal choice of first-line treatments, but after progression the therapeutic possibilities and the criteria for choice are different. Areas covered: The purpose of this literature review is to discuss the different possibilities of second-line treatment and to specify the criteria for choice. Biological subgroups requiring specific therapeutic decisions will be described. We conducted a systematic review for randomized controlled trials published since 1995. A non-exhaustive review of published phase II studies, cohort studies, and international guidelines was also given and future leads were discussed. Expert opinion: Some choices of second-line treatments are a direct result of the option chosen in the first line. Others are necessary because of the biological specificity of the tumor: immunotherapy for tumors with microsatellite instability, or the combination encorafenib cetuximab for mutated BRAF-V600E tumors. In many other circumstances, there are several options that require extensive involvement of multidisciplinary boards and the patient in the final therapeutic decision.